UJI DAYA ANTELMINTIK INFUSA BIJI WALUH (Cucurbita moschata Durch) TERHADAP CACING Ascaridia galli SECARA IN VITRO - mohammad djatmiko; lusi dwi purnowati; suhardjono suhardjono (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2009)
ABSTRACTWormy represent one of factor which can degrade human resource quality, considering wormy will persue physical growth and also work productivity. Research which is taken is experimental research as a mean to know energy of antelmintik infusa of pumpkin seed toward worm Ascaridia galli by in vitro and also its active compound content. Substance intake by random and then sampling is made in infusa supply with a few concentration series that is hereinafter tested by its activity as antelmintik to worm Ascaridia galli with immersion method. The data observed is time of worm death and sum up the dead worm every one clock. Statistic analysis which is used is Kruskal-Wallis continued by Mann-Whithney and also Anova and continued by Tukey. Result of research indicate that mean of time of worm death of Ascaridia galli after soaked in infusa of pumpkin seed in concentration 2,5%b/v, 5,0%b/v, 7,5%b/v, 10,0%b/v and successively is 9,46; 8,63; 6,08; and 5,83 clock. While after soaked in piperazin sitrat of concentration 0,4%b/v and NaCl 0,9%b/v mean of time of worm death is 8,96 and 32,37 hours. All series of concentration of infusa of pumpkin seed in this research own difference that has a meaning negative control of Nacl 0,9%b/v, so that infusa of pumpkin seed equal to 7,43%b/v while value of LC50 after soaked in piperzin sitrat 0,73%b/v. Result of KLT inspection indicate that infusa of pumpkin seed contain compound of powered saponin of antelmimtik. Keyword : Infusa of pumpkin seed, antelmintik energy, worm of Ascaridia galli.